Developing and evaluating an intelligent integration system for older adult care and health based on the sport-medicine-tourism model - Ma, Xiaoxue; Fang, Xiaofei; Liu, Shuqian; Wang, Xueqing; Wang, Ping; Jiang, Fugao (Frontiers in Public Health, 2025)
This study develops a comprehensive intelligent integration system for older adult care and health by combining resources from sport, medicine, and tourism. The research aims to address the dual challenges of population aging and the transformation of older adult care services in the digital era. The study follows a five-stage research framework: theoretical construction, user needs identification, system design, prototype modeling, and empirical evaluation. A 12-month quasi-experimental study was conducted with 300 older adult participants from Jinan, Qingdao, and Rizhao in China, utilizing both control and experimental groups. Physical health, psychological well-being, social participation, and quality of life were measured using standardized scales (GDS-15, SWLS, WHOQOL-BREF), while system performance was assessed using the Analytic Hierarchy Process and fuzzy comprehensive evaluation. The findings demonstrate significant improvements in the experimental group across all health dimensions (p < 0.05), and the system was rated as “Good” in functional utility, service quality, and user satisfaction. However, deficiencies in tourism service comfort remain and require further optimization. This study contributes a novel SMT-based integration model supported by STS theory and actor-network modeling, offering theoretical insight and empirical evidence for the design of intelligent older adult care systems in aging societies.